Instrumental Activity of Daily living in war related bilateral lower limb amputation - M.R. Soroush; Z. Ganjparvar; M. Masoumi; B. Mousavi (Afarand Scholarly Publishing Institute, 2012)
Objective(s): Independency in life activities has an important role in individuals with disability to bring them back to normal life. The objective of this study was to determine Instrumental Activity of daily Living in survivors of the Iran-Iraq war with bilateral lower limb amputation. Methods: A cross-sectional study was performed to assess the level of Instrumental Activity of daily Living (IADL) - Lawton and Brody IADL scale questionnaire- in Iran-Iraq war related bilateral lower limb amputees (n=335). The Chi-square test was employed as statistical methods. Data were analyzed using SPSS software. Results: The average age of the patients was 42.05 (SD=6.33).The majority of the cases %97.6 (n=327) were male and married. The most dependency in IADL were housekeeping (91.3%), food preparation. And the least was ability to use telephone (4.2 %). Age, level of education, employment status, co morbidity, phantom pain and its severity and duration was significantly (P≤0.05) associated with Instrumental Activity of daily Living scale. Conclusion: This study showed that war related bilateral lower limb amputees were dependent in some IADL scales, especially housekeeping and food preparation. Rehabilitation programs might help the amputees to be more independent in their normal life activity.